Impact of licorice root on the burn healing process: A double-blinded randomized controlled clinical trial - Mohsen Zabihi; Bahareh Hatefi; Mohammad Ebrahimzadeh Ardakani; Ali Mohammad Ranjbar; Farhad Mohammadi (Elsevier, 2023)
Ethnopharmacological relevance: Due to the known side effects of many synthetic drugs, the use of herbal and natural substances in treating diseases such as burns has been considered. licorice is a herbal medicine whose stem and underground roots are used in traditional medicine in many countries, including Iran, for anti-inflammatory, stomach ulcer healing, and antimicrobial purposes. Aim of the study: This study investigated the healing effect of hydroalcoholic extract of licorice root on the wound healing process caused by second-degree burns. Methods: The hydroalcoholic extract of licorice was prepared in ethanol solvent, and then the licorice hydrogel product was designed using gelling compounds. Then, in a double-blinded randomized clinical trial, 50 patients with second-degree burns were selected based on inclusion criteria from the patients referred to Yazd Hospital and Isfahan Hospital. Participants were randomly divided into two groups: the control group receiving hydrogel without extract and the intervention group receiving hydrogel containing licorice root hydroalcoholic extract. The intervention lasted for 15 days, and during this period, the wound-healing process was evaluated on days 1, 3, 6, 10, and 15. Data were analyzed using SPSS software with independent T-test and Mann-Whitney U tests with a maximum error of 5 %. Results: The rate of inflammation (From the 3rd day to the 10th day), redness (From the 6th day to the 15th day), pain (on the 3rd day), and burning (From the 3rd day to the 15th day) of the wound in the group that used the hydrogel-containing hydroalcoholic extract of licorice root was significantly lower than in the control group (P < 0.05), and the healing process was significantly faster than the control group. Conclusion: Hydroalcoholic extract of licorice root can accelerate the healing process of second-degree burns.